Perspektif Filsafat Ilmu dalam Islamisasi Ilmu Pengetahuan Dikalangan Ilmuan Muslim - Budi Harianto (UIN Sumatera Utara, 2023)
Very important in humans. Science is a way of thinking of humans and is used to separate Science helps humans to orient themselves in the world and solve various life problems. Problems that make them do not know how to develop themselves. Therefore, knowledge is humans from other creatures. process of human thinking and is used as a barrier between humans and other living things. In the beginning, everything that humans did was because human nature in their life has a noble purpose in life that is higher than mere existence. That's why humans always try to develop science. The philosophy of science can be used as a perspective in the idea of Islamization of science because at this time what has developed lately is one branch of philosophy that aims to realize the relationship between science and philosophy. By making the Philosophy of Science as a perspective, benchmark, or establishment in order to analyze and develop the framework of Islamic science, using the approaches and methods that exist in philosophy. Only used for the Islamization of knowledge.